Trust and mistrust in the relations between Zimbabwean security guards and South African residents of a phepha gated complex in Johannesburg - Nkombyane, Tsakani (My University, 2017)
This research report explores how the notion of mistrust towards the migrant security workers in a Gated Complex is perceived by South African citizens. By drawing on interviews with the security guards during on ethnographic fieldwork within the specific residential complex, the findings suggest that the reasons for mistrust are fixed within the social contexts from which immigrants come from and where they are living. Therefore, even though the security guards are on a mission to secure the complex, without trust from the securitised, their work is fruitless. Thus, this investigation will question the expectation that leads to trust and mistrust on both the guards and the tenants.
A research report submitted in partial satisfaction of the requirements of the degree Master of Arts in Anthropology March 2017
Keywords: South Africa--Employment Equity Act, 1998.; Security guards--South Africa; Foreign workers--Legal status, etc; Migrant labor--Legal status, laws, etc